Analisis Efektivitas Program Onboarding Terhadap Retensi Karyawan - Dora Indah Triana (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to evaluate how effective onboarding programs are in retaining employees in an organization and determine the extent to which onboarding programs contribute to employee retention within a company. This research is usually conducted to ensure new employees feel integrated, supported, and motivated, thereby increasing retention and reducing turnover. This abstract will present the research methodology, such as data collection through questionnaires and statistical analysis, as well as results that show the relationship between effective onboarding programs and increased employee retention. The problem faced is that a high employee turnover rate can cause instability and increase recruitment and training costs. An effective onboarding program can address this by making new employees feel more valued and engaged with the company. The conclusions from this research can also identify specific factors in the onboarding process that most influence retention, such as cultural aspects, connections with colleagues, and task clarity.